2015
DOI: 10.1063/1.4939267
|View full text |Cite
|
Sign up to set email alerts
|

Continuous sheath-free separation of particles by shape in viscoelastic fluids

Abstract: Shape is an important indicator of cell type, cycle, and state, etc., and can thus serve as a specific marker for label-free bioparticle separation. We demonstrate in this work a shape-based separation of equal-volumed spherical and peanut particles in viscoelastic fluids through straight rectangular microchannels. This continuous sheath-free separation arises from the shape-dependent equilibrium particle position(s) as a result of the flow-induced elasto-inertial lift and shear thinning effects. A continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 53 publications
10
50
0
Order By: Relevance
“…Specifically, at the lowest flow rate tested in this work (e.g., 1 μl min −1 ), both the fluid inertia and the Dean flow can be neglected (Re c ∼ OIJ0.01) ≈ 0, De ∼ OIJ0.001) ≈ 0, see the ESI † Table S1 for the detailed values of the calculated dimensionless numbers) and the particle lateral migration is dominated by the fluid elasticity effects (Wi ∼ OIJ0.1), El > 1). 13,16 Instead of single-line focusing, the particles in low-aspect-ratio straight channels would equilibrate at two central symmetric positions which then evolve to become three with an additional one at the channel center at a slightly higher flow rate, as found in previous studies 16,34 and our work (see Fig. The stronger elastic force vector in the vertical direction first moves the particles to the center plane along the channel height.…”
Section: Discussionsupporting
confidence: 68%
“…Specifically, at the lowest flow rate tested in this work (e.g., 1 μl min −1 ), both the fluid inertia and the Dean flow can be neglected (Re c ∼ OIJ0.01) ≈ 0, De ∼ OIJ0.001) ≈ 0, see the ESI † Table S1 for the detailed values of the calculated dimensionless numbers) and the particle lateral migration is dominated by the fluid elasticity effects (Wi ∼ OIJ0.1), El > 1). 13,16 Instead of single-line focusing, the particles in low-aspect-ratio straight channels would equilibrate at two central symmetric positions which then evolve to become three with an additional one at the channel center at a slightly higher flow rate, as found in previous studies 16,34 and our work (see Fig. The stronger elastic force vector in the vertical direction first moves the particles to the center plane along the channel height.…”
Section: Discussionsupporting
confidence: 68%
“…This phenomenon indicates the strong shapedependence of the flow-induced elasto-inertial lift, which, through a high-speed imaging of particle motion, is speculated to correlate with the rotational effects of non-spherical particles. Lu et al [130] later found that the differential elasto-inertial focusing, which had been demonstrated to separate particles by size in a sheath-free manner [110], is also capable of separating the spherical and peanut particles in 1000 ppm PEO solution flow at greater than 95% efficiency and purity (Fig. 11b).…”
Section: Separation Based On Other Intrinsic Markersmentioning
confidence: 99%
“…For most commonly‐used viscoelastic fluids, N2false(trueγ̇false) is very small and thus can often be neglected under most flow conditions . Therefore, the positive N1false(trueγ̇false) generates an elastic force FEap3N1false(trueγ̇false)8ap3λQ3/(hw2)3 (where λ is the relaxation time of viscoelastic fluids) on particles in the direction of decreasing shear rate . When the shear thinning effect is weak, the particles would migrate towards five cross‐sectional positions (four corners and one center) where the shear rates are at the minimum.…”
Section: Methodsmentioning
confidence: 99%